TIKTOK AS A MEDIUM FOR LEARNING ENGLISH PRONUNCIATION: EXPLORING THE PERCEPTIONS OF UNIVERSITY STUDENTS - Marietta Simbolon, Ernia; Novitri, Novitri; Azhar, Fadly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines university students’ perceptions of TikTok as a medium for learning English pronunciation. The research was conducted due to the increasing use of social media platforms in language learning and the limited studies focusing on students’ perceptions of TikTok specifically for pronunciation practice. A quantitative research design was employed, and data were collected through a closed-ended questionnaire adapted based on previous research and developed based on the Technology Acceptance Model (TAM), which includes Perceived Usefulness (PU), Perceived Ease of Use (PE), and Attitude Toward Using (ATU). The participants were 66 fourth-semester students of the English Department at Universitas Riau who actively use TikTok. The collected data were analyzed using descriptive statistical analysis, particularly mean score calculation. The findings reveal that students’ perceptions across all three TAM indicators fall within the High category. The results indicate that students perceive TikTok as useful in supporting pronunciation learning through its short videos, clear audio input, visual demonstrations, and interactive features. TikTok is also perceived as easy to use and accessible content, which allows students to practice pronunciation efficiently. In addition, students demonstrate positive attitudes toward using TikTok, showing motivation, enjoyment, and willingness to incorporate the platform into their pronunciation learning activities. Overall, the findings suggest that TikTok is perceived as a beneficial, user-friendly, and well-accepted supplementary medium for learning English pronunciation in higher education contexts.